The ‘Red Tricontinental’, the Gaullist illusory of an international conspiracy (1968-1974) - Muller, Bryan (Lyuboslovie, 2024)
Traumatised by the events of May-June 1968, the French government majority (the Gaullists and their liberal allies, joined by a centre-right minority the following year) relied on the Ministry of the Interior and certain militant Gaullist organizations (the ‘Gaullists of Order’) to confront the ‘revolutionary’ movements. Interior Minister Raymond Marcellin conceived the myth of the ‘Red Tricontinental’ [‘Tricontinentale rouge’], a sort of sprawling international Marxist conspiracy, to explain past unrest, discredit it with the idea of outside intervention and justify increased repression. The ‘Gaullists of order’ shared the fear of ‘Marxist subversion’ at work and supported the repressive actions of the Minister of the Interior. ‘Marxist subversion’ turned to be a two-pronged operation carried out by left and far-left organizations (socialists, communists, Trotskyists, Maoists, anarchists), consisting of infiltrating state institutions in order to modify them - discredit them - from within, and diverting attention by mobilising more radical elements through agitation and propaganda. Foreign powers (the USSR and its satellites, Maoist China and/or Cuba) are said to be supporting, or even directing, this operation behind the scenes. This interpretation is phantasmatic, there is no subversion at work. However, many managers and activists are convinced of this reality. Others, more rare, are aware from the start of the reality of the facts and lie on purpose to manipulate public opinion in their favour. The idea of a ‘Red Tricontinental’ was illusory, both for part of the activists and part of the electorate, between political manipulation and partisan autointoxication.